2016
DOI: 10.1515/pjct-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative decomposition of methanol in a vibroacoustic fluidized bed of Ag-coated cenosphere core-shell catalyst

Abstract: The paper presents results of a study of oxidative decomposition of methanol in a fl uidized bed of silver catalyst. The process of methanol oxidation was carried out on Ag-coated cenospheres core-shell catalyst. The catalyst was obtained by precipitation of silver from methanolic solution of silver nitrate on cenospheres. Cenospheres are lightweight, inert, hollow spheres, which can be easily introduced into a fl uidized bed. Application of the catalyst in a form of fl uidized bed should ensure good temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…S1231-S1240 S1233 locity of grains of the catalyst is reduced and the contact time between fluidising medium and grains is increased. Previous studies have shown that oxidation of methanol can be successfully carried out on Ag-coated cenospheres having a core-shell structure [41]. It turned out, however, that the silver deposited on aluminosilicate microsphere is not resistant to abrasion, which resulted in silver particles of the shell being removed from the fluidised bed.…”
Section: Cenospheres As a Catalyst Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…S1231-S1240 S1233 locity of grains of the catalyst is reduced and the contact time between fluidising medium and grains is increased. Previous studies have shown that oxidation of methanol can be successfully carried out on Ag-coated cenospheres having a core-shell structure [41]. It turned out, however, that the silver deposited on aluminosilicate microsphere is not resistant to abrasion, which resulted in silver particles of the shell being removed from the fluidised bed.…”
Section: Cenospheres As a Catalyst Carriermentioning
confidence: 99%
“…The fluidisation process was supported by sounds emitter with a frequency of 45 Hz. It facilitated achieving the minimum fluidisation velocity at low flow speed of gas [40] and also prevented formation of channels in the bed, local areas of overheating of the catalyst [41]. Liquid methanol (2-18 cm 3 /h) and a solution of N 2 O (72 cm 3 /min.)…”
Section: Experimental Arrangementmentioning
confidence: 99%